Comparative efficacy of ivermectin, albendazole, levamisole and rafoxanide against gastrointestinal nematode infections in goats - WARUIRU, R M; NGOTHO, J W; MUTUNE, M N; MUNYUA, W K (The Indian Journal of Animal Sciences, 2014)
A study on the efficacy of 4 anthelmintics was carried out using aifaecal egg count reduction test (FECRT) in 107 goats on a breeding farm at OI’Magogo, Naivasha, Kenya. The goats were randomly assigned to 7 groups; the first acted as untreated controls and the other groups received ivermt;ctin (IVM) @ 0.2 mg/kgbodyweight once orally, albendazole (ABZ) @ 5.0 mg/kg, levamisole (LEV) @ 15 mg/kg and rafoxanide (RFX) @ 15 mg/kg orally as 2 doses 24 hr apart. Other groups received albendazole and levamisole (ABZ+LEV) and levamisole and rafoxanide (LEV+RFX) at the same doses and schedules as and when used individually. Faecal egg counts were measured at treatment (day 0) and 10 and 21 days afterwards. Decreasing efficacies, as measured by 3 different formulae were recorded at day 21 for IVM, ABZ and ABZ+LEV (>96%), LEV (<54%), RFX (<60%) and LEV+RFX (<65%). Calculations of 95% confidence limits indicated that resistance was present in the LEV, RFX and LEV+RFX groups. The predominant use of LEV on the farm for a long period at dose rates recommended for sheep may have contributed to the development of resistance.